Enhancement of spin Seebeck effect of reverse spin crossover Fe (II) micellar charge transport using PMMA polymer electrolyte - Megat Hasnan, Megat Muhammad Ikhsan; Mohd Noor, Ikhwan Syafiq; Nayan, Nafarizal; Ahmad, Mohd Khairul; Mohd Said, Suhana; Mohd Sabri, Mohd Faizul; Mohd Salleh, Mohd Faiz; Mohamed Ali, Mohamed Sultan; Mohd Zin, Rosnah (John Wiley and Sons, 2021)
The electrochemical thermoelectric effect is capable of generating Seebeck and conductivity from a temperature gradient through redox reaction at the electrode. Conventional spin Seebeck effect (SSE) is the generation of spin voltage by solid coupling magnetic thin film in presence of magnetic field and temperature gradient. In this study, we demonstrate an enhancement of a magnetic free SSE of Fe (II) reverse spin-crossover in electrolyte using 1% PMMA polymer additive in form of polymer electrolyte. The reverse spin effect of Fe (II) complex, which is confirmed by SQUID magnetometer analysis and DFT simulation, is able to produce magnetic free SSE in solution. A unique electrochemical behavior is found in form of SSE Fe (II) polymer electrolyte that is elucidated using cyclic voltammetry, electrochemical impedance spectroscopy, and UV-Vis analysis. The polymer electrolyte that possesses strong spin Seebeck produces a maximum Seebeck coefficient and conductivity of 124 % and 233 % higher than that weak SSE and conventional liquid electrolyte. The spin Seebeck produces a high number of carrier density through fast diffusion at high spin state, and the opposite charge properties trend at low spin state. Cryo-TEM analysis had shown that the generation of spin Seeebeck effect of the Fe (II) complex in solution also involves reverse spherical micelles formation. Thus, this study highlights the finding of a rare magnetic free spin Seebeck generation in polymer electrolyte that having potential for waste heat recycles, heat sensors, and thermal switches applications upon development.